An association of low-density lipoproteins and fibrinolysis in patients with severe aortic stenosis- valvular expression of fibrinolytic proteins. (14th October 2021) - Kopytek, M; Undas, A; Natorska, J
Abstract: Background: Aortic stenosis (AS) is associated with hyperlipidemia and hypofibrinolysis. The contribution of serum lipids to the valvular expression of fibrinolytic proteins is not known. Aims: To evaluate whether fibrinolytic factors are present within stenotic aortic valves and to determine their potential associations with LDL cholesterol concentrations, their oxidized forms (oxPL-LDL), and AS severity. Methods: We enrolled 75 patients with isolated severe AS aged 66±8 years (mean gradient 52 mmHg, max gradient 84 mmHg) undergoing valve replacement surgery. Aortic valve leaflets obtained from AS patients (n=30) and from age-matched healthy autopsy donors (n=3) were used to evaluate in loco the presence of plasminogen (PLG), tissue plasminogen activator (tPA), and fibrinolysis inhibitors (α2-antiplasmin and plasminogen activator inhibitor, PAI-1). PLG activity, plasma tPA and PAI-1 levels, along with cholesterol and oxPL-LDL were assayed. Clot lysis time (CLT) was performed to assess the overall fibrinolytic system activity. Results: AS patients with LDL cholesterol ≥3.0 mM (n=25, 56% taking statin) compared to those with LDL cholesterol <3.0 mM (n=50, 86% taking statin) had higher oxPL-LDL levels (+80%, p=0.0014). Moreover, AS subjects with LDL cholesterol ≥3.0 mM, compared to those with LDL cholesterol <3.0 mM had longer CLT (+22.4%, p=0.0022) along with higher plasma tPA (+31.5%, p=0.004) and PAI-1 (+47.4%, p=0.01), while PLG activity tended to be higher (+10.8%, p=0.056). For the first time the valvular expression of fibrinolytic proteins was detected in AS patients, but not in healthy donors. The expression of studied proteins was observed mainly on the aortic side of the leaflets and only trace amounts were detectable in deeper layers of valves. The valve area positive for PLG was 4.4±1.8%, for tPA 1.6±0.8%, while the expression of α2-antiplasmin was 4.2±1.7% and 6.9±2.3% for PAI-1. In the whole AS group, oxPL-LDL, but not LDL cholesterol showed associations with mean (r=0.34, p=0.041) and max (r=0.3, p=0.016) gradients. Serum concentrations of LDL cholesterol correlated with CLT (r=0.42, p=0.0002), blood PLG activity (r=0.56, p=0.0012) and with tPA (r=0.43, p=0.0001) and PAI-1 (r=0.32, p=0.006) levels. Similarly, oxPL-LDL were associated with CLT, PLG activity, and tPA (r=0.34; r=0.59; r=0.47, all p<0.01). Valvular expression of fibrinolytic proteins did not correlate with LDL cholesterol, ox-PL-LDL or transvalvular gradients. Conclusions: This study is the first to demonstrate that in AS patients hypercholesterolemia and enhanced lipid oxidation are associated with impaired systemic fibrinolysis, which supports the concept of beneficial effects of cholesterol-lowering therapy in mild-to-moderate AS. Moreover, valvular expression of fibrinolytic factors suggests that these factors are delivered with circulating blood but not synthesized de novo. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre (NCN)